ANALISIS PENERJEMAHAN LAFADZ MUSYTARAK LAFDZI DALAM FILM AHMAD BIN HANBAL BERDASARKAN TEORI KODE PESAN ROMAN JACOBSON - Yuni Lutfiani Lutfiani; Akmaliyah Akmaliyah; Amiq (Hijai - Journal on Arabic Language and Literature, 2025)
Translating Arabic texts into Indonesian involves a good understanding of semantics. One challenge in translation is selecting the correct meaning for polysemous words (musytarak lafdzi). This study aims to analyze the translation of polysemous words in the film Ahmad bin Hanbal using Roman Jakobson's message code theory. The research method is descriptive qualitative, with data collection techniques including citation and documentation. The data analysis process involves data reduction, presentation, and conclusion drawing. The results show several polysemous words in the film, translated as follows: صنعة as "profession," فتن as "destruction," ديار as "country," خذوه as "take him," جرى as "result," and عرض على as "offering." This study on the translation of polysemous words contributes to the development of semantic studies, particularly in understanding meaning relations related to translation quality. Keywords: Translation, Semantics, Polysemous Words, Message Code Theory